2022
DOI: 10.3390/agronomy12081943
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Photosynthetic Pigment Characteristics, Mineral Content, and Antioxidant Activity of Lettuce (Lactuca sativa L.) by Arbuscular Mycorrhizal Fungus and Seaweed Extract Foliar Application

Abstract: Beneficial plant–microbe interaction for enhancing crop yield and quality is a sustainable way to achieve eco-friendly, desirable agricultural productions. The main objective of this experiment was to evaluate the individual and combined effects of an arbuscular mycorrhizal fungus (AMF) strain (Funneliformis mosseae) and a seaweed extract (SWE) derived from Ascophyllum nodosum, on the growth and physiological responses of lettuce (Lactuca sativa L.). Lettuce plants were inoculated with commercial AMF inoculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 76 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…High total soluble carbohydrates content in the leaves inevitably improves the nitrate assimilation pathway 52 . The enhancement of carbohydrates concentration in AMF-treated plants may be described by the enhanced carbon fixation and the activation of several enzymes 32 . Finally, AMF inoculation improved the net photosynthetic potential as well as the carbohydrate content in Zenia plants 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High total soluble carbohydrates content in the leaves inevitably improves the nitrate assimilation pathway 52 . The enhancement of carbohydrates concentration in AMF-treated plants may be described by the enhanced carbon fixation and the activation of several enzymes 32 . Finally, AMF inoculation improved the net photosynthetic potential as well as the carbohydrate content in Zenia plants 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In the peppermint plant, AMF treatment improved the root colonization, growth, essential oil yield, and nutrient acquisition of the plant 30 . In addition, the arbuscular mycorrhizal fungus increases the efficiency of photosynthesis in the host plant, and it has been reported that the quantitative and qualitative characteristics of the lettuce plants were significantly affected by the SWE and AMF co-treatments 31 , 32 . Also, in coriander, in addition to the positive effects on biomass performance and root colonization; AMF significantly increased the alpha-pinene content compared to control plants 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The growth of plants under environmental stresses leads to oxidative stress, causing a pathological condition. Numerous studies have confirmed the existence of a strong relationship between the number of microbes and the total antioxidant capacity in the soil and different soil types [92,93].…”
Section: Biological Activities In the Rhizosphere Of Barley Plants Un...mentioning
confidence: 96%
“…The chlorophyll and carotenoid content of non-green leaves in A. kolomikta and A. polygama was chemically determined by the method of Asadi et al (2022). Chlorophyll was extracted with ice-cold acetone/tetrahydrofuran (1:1, v/v) and filtered through a 0.22 μm membrane filter.…”
Section: Measurement Of Leaf Reflectance and Pigmentmentioning
confidence: 99%